STRATEGI KKN DALAM MENGATASI KEKURANGAN TENAGA PENDIDIK MELALUI PROGRAM PENDAMPINGAN DAN KELAS KREATIF DI SMP NEGRI 2 LAPPARIAJA DESA BENGO - Sarfiana Yasse; PERDIANTO; Musdalifa; Ismail Syam; Renita; Muh. Fairul Arsal; Ririn Ramadanil; A. Riswandi T.; Muhammad Yany (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) is one of the students’ contributions to society aimed at supporting educational development in rural areas. This article discusses KKN strategies to address the shortage of teaching staff through tutoring programs and creative classes at SMP Negeri 2 Lappariaja, Desa Bengo. The program was designed to improve the quality of learning, broaden students’ access to knowledge, and stimulate their learning motivation. The methods used included identifying the needs for teaching staff, developing creative learning modules, conducting direct classroom assistance, and evaluating learning outcomes. The results of the program showed increased student participation, improved academic performance, and the creation of a more innovative learning environment. This activity demonstrates that the involvement of KKN students can serve as an alternative solution in sustaining education in regions facing teacher shortages.